Inpatient Prenatal Yoga for Hospitalized High-Risk Antepartum Patients: A Feasibility Study [1Q]. (May 2017) - Demtchouk, Veronica; Kelly, Jeannie; Prigo, Corinne; Dangel, Alissa
Abstract : INTRODUCTION: Prenatal yoga has been shown to be a safe and effective treatment for depression and pain, while improving high-risk pregnancy outcomes. This study investigated the feasibility of establishing a prenatal yoga program for hospitalized high-risk antepartum patients. METHODS: Patients admitted for at least 72 hours to the antepartum service at a tertiary care center were screened for eligibility and consented. Additional medical clearance was obtained from their primary obstetrician. A 30-minute prenatal yoga session was held once a week by a certified prenatal yoga instructor. Physical activity level was adapted to accommodate patients on modified bed rest. Participants completed a questionnaire following the conclusion of each session addressing class timing, length, and frequency. Antepartum nurses were also surveyed to evaluate their perspective. RESULTS: The majority of antepartum patients hospitalized for pregnancy-related complications were offered participation. Of these, 34 women consented and were eligible to participate; 13 attended at least one session during their hospitalization. Others did not participate due to scheduling conflicts with fetal testing, change in clinical status, lack of interest the day of, and delivery or discharge. Post session patient surveys revealed that all patients enjoyed class length and frequency and viewed them as beneficial for managing stress, musculoskeletal discomfort, and sleep quality. Nursing surveys revealed the class did not affect their ability to provide medical care for the patients. CONCLUSION: Inpatient prenatal yoga is a feasible and acceptable intervention for high risk women admitted for antepartum management. Future study of the effect on maternal and fetal outcomes should be strongly considered.